x + 7y = 39 ....... Eq.1
3x - 2y = 2 ....... Eq.2
multiply Eq.1 with (-3) and so Eq.1 will be :
-3x - 21y = -117
3x - 2y = 2
_________________ by Elimination method ( Eq.1 + Eq.2 ) the result will we :
- 21y - 2y = - 115
-23y = -115
Y = 5
to find the value of x, put the value of y in Eq.1 :
x + 7y = 39
x = 39 - 7y
x = 39 - 7(5)
X = 4
___________________________________________________________
you can solve it in another way by using substitution method:
x + 7y = 39 ....... Eq.1 ,, you can write it in another form, x = 39 - 7y
3x - 2y = 2 ....... Eq.2
Put the value of Eq.1 on Eq.2
3(39 - 7y) - 2y = 2
117 - 21y - 2y = 2
117 - 23y = 2
23y = 115 ............ Y = 5
to find the value of X , put the value of Y in Eq.1
x = 39 - 7y
x = 39 - 7(5)
x = 39 - 35 .............. X = 4
and so in both ways....you got the same answer choose the easiest way for you :)
good luck my friend...
Chat with our AI personalities
2nd z=17 1st Z=22 Easy as ABC: Just do the following 39-5=___ ___divide by 2=z z+5=Z
2x + 6 + 9x = 39 11x + 6 = 39 11x = 39 - 6 11x = 33 x = 3
x+7y=39
-39 minus -26 is -13
3x-8+5x+39+4x+51 = x(3+5+4) + -8 + 39 + 51 = 12x +82